A 5 year retrospective analysis of adverse drug reactions associated with antimicrobials in a teaching hospital of Andaman and Nicobar islands - Mangesh Bankar; Priyanka Pravinbhai Hotha; Nimisha Elezebeth Zachariah (Universitas Ahmad Dahlan, 2021)
Antimicrobials are used widely especially in developing countries, due to the high prevalence of various infectious diseases. Inappropriate use of antimicrobials are associated with adverse drug reactions. The present study was done to analyze the patterns of Adverse Drug Reactions (ADR) due to antimicrobials reported to Adverse Drug Reaction Monitoring Centre (AMC) during the last five years.Â This was a 5 year retrospective and cross-sectional study. After collecting demographic details of patients, ADR forms, and ADR associated with the antimicrobial class of drugs, data were analyzed for further details. A total of 877 ADRs, 360 ADRs belonged to the antimicrobial group. When data was analyzed data, it revealed that the majority of ADRs (73.05%) were reported in the adult group, 75.27% of reactions belonged to A category, Ceftriaxone (17.2%) was the most common drug-associated with ADRs, majority of ADRs were related to skin (56.66%), rash (27.5%) was the most common ADR encountered with antimicrobial use, 73.61% reactions were non-serious, 69.44% of ADRs recovered, and 77.77% of ADRs were probable category. Ceftriaxone was responsible for the maximum number of ADRs. The study results provide information regarding the pattern of ADRs associated with antimicrobials, and this might be helpful for improving the awareness of healthcare providers about PvPI and subsequently increase the spontaneous reporting of ADRs.